BEDA EFEKTIFITAS METODE BUGNET EXERCISE DENGAN METODE WILLIAM FLEKSION EXERCISE PADA PASIEN NYERI PINGGANG BAWAH DI KLINIK FISIOTERAPI RATULANGI MEDICAL CENTRE MAKASSAR - Suharto Suharto; Arpanjam’an Arpanjam’an; Suriani Suriani (Politeknik Kesehatan Makassar, 2017)
Low back pain is a common complaint in everyday practice. It is estimated that almost everyone has experienced low back pain during his lifetime. The cause of low back pain is very diverse from mild to severe and very serious. In Indonesia, lower back pain is found at the age of 40 years. In developed countries the prevalence of low back pain is about 70-80%. Although rarely fatal but the perceived pain causes the patient to experience limitations in daily activities and many loss of working hours, especially in the productive age, so that is the most reason in seeking treatment.This study aims to determine the Differences Effectiveness between Bugnet Exercise method with William Fleksion Exercise method on the application of Infra Red Rays Patients with Lower Waist Pain with quasi experimental and pre-test research design - post test two groups of 20 people each method 10 research subjects randomly Sampling. Both groups were measured by using Visual analog scale before and after treatment. The results of the study were 50% aged 31-40 and 50% aged 41-60 years. In the research subjects given IRR and Bugnet exercises obtained p value = 0.000. While given IRR and William flexion exercises obtained p value = 0.005. In the Mann Whitney Test test, p = 0.052> α = 0.05, which means there is no significant difference between the two methods to decrease the actuality of lower back pain but IRR with William flexion exercises has a greater mean value of change that is 3,350 ± 0.66841 cm than the group IRR treatment with Bugnet Exercise method is 3,300 ± 0.66173 cm. It was concluded that IRR with William flexion exercises better results in decreased pain in patients with lower back pain. Keywords: Bugnet exercises, William flexion, Lower back pain